Dislocation dipole-induced strengthening in intermetallic TiAl. (15th January 2018) - He, Yan; Liu, Zhao; Zhou, Gang; Wang, Hao; Bai, Chunguang; Rodney, David; Appel, Fritz; Xu, Dongsheng; Yang, Rui
Abstract: Narrow dislocation dipoles in intermetallic TiAl are systematically investigated by atomic-scale simulations and electron microscopy. The formation energy of narrow dipolar configurations and the activation energy during their evolution are unraveled. We show that faulted dipoles can be stable over experimental timescales, in full agreement with high-resolution observations. Such stable atomic-scale structures provide a strengthening effect significantly larger than the elastic prediction, which deeply influences plasticity in TiAl. Graphical abstract: Image 1